Quem é que fala nos filmes de Lucrecia Martel? O olhar, a narrativa, o narrador e o ponto de vista - Nantes, Josiane Valcarenghi Ribeiro (2018)
This dissertation aims to reflect on the narrative construction, narrator and point of view in Lucrecia Martel's feature films, specifically “La ciénaga” (2001), “La niña santa” (2004) and “La mujer sin cabeza” (2008). Considering that the above mentioned works were produced at a historical moment called Postmodernism, some theorists are used to determine this concept, and thus to realize that this period determines and influences many of the fields of social life, including the arts and its aesthetic framework. The narrative, the narrators and the point of view of these filmmaker's works are part of this group, and therefore a more in-depth study of the postmodern issues is justified. Lucrecia Martel has a peculiar way of filming and constructing her narrative space – the sense of disorder is constant –, consequences of the use of the flow narrative. In addition, she also uses orality techniques, making her works to be complex, not only in their compositional structure, but thoroughly. Their narrators are hybrids, as well as the point of view used to tell/show their fiction. Postmodern works are constructed without limiting boundaries. They slide between the various artistic fields, making the cultural representations fragmented, ephemeral and fluid, remnants of the social structure. For theoretical basis, the propositions of Fredric Jameson ([1991] 1996), David Harvey ([1989] 2008) and Linda Hutcheon ([1988] 1991) are sought to address the questions of Postmodernism. Silviano Santiago ([1989] 2002) and Flavio de Campos ([2007] 2009), regarding the specifications of the narrators, Norman Friedman ([1967] 2002) as for the specification of the point of view, and, when necessary, by way of theoretical comparison, other authors dealing with these subjects. This way, it is intended to discuss and undertake the delineation of how the narrative, the narrator(s) and the point of view in the cinematographic works are constructed in Lucrecia Martel's films.